MRI evaluation on exit foramina and lateral recess in patients who undergo posterior lumbar interbody fusion in Hospital Raja Perempuan Zainab II - Hassan, Siti Aisah (2011)
Background: Low back pain due to degenerative lumbar spine is one of the most common presenting complaints in out-patient and orthopaedic clinics. While most cases usually resolve in few weeks, 2% of them develop radiculopathy and need further radiological investigations. Regardless of age and occupation of patients, back pain is a common cause of disability and gives a great personal and social impact to the individual and families, and economic burden to the society. Magnetic Resonance Imaging (MRI) is the gold standard imaging modality for investigation of degenerative disc disease for its superior soft tissue contrast, multiplanar imaging capability and non-ionizing property. Changes of degenerative intervertebral discs are well-demonstrated. Disc herniations, thickened ligamentum flavum and osteophytosis cause narrowing of neuroforamina, and further compromise the spinal cord and exiting nerve roots. Therefore, MRI is valuable to determine the degree of stenosis and level of compression, and hence, used as a guide to aid plan of surgical decompression. Posterior Lumbar Interbody Fusion (PLIF) is one of the surgical technique of nerve root decompression using posterior approach. In PLIF procedure, incision is made at midline at the back. This is followed by laminectomy to gain access to the intervertebral disc space. Discectomy is then performed and disc materials are replaced with disc spacer to restore disc height. It was postulated that PLIF procedure is able to restore foraminal height and therefore relieved nerve root compression without foraminotomy. Objectives: To study the improvement of exit foramina and lateral recess stenosis in patients with back pain who underwent Posterior Lumbar Interbody Fusion (PLIF), using MRI as diagnostic tool, to correlate the MRI findings with clinical symptoms and to determine whether disc spacer height is a good predictor for improvement of lateral recess and exit foramina. Methodology: It is a cross-sectional, observational study of patients with back pain due to degenerative disc disease who underwent Posterior Lumbar Interbody Fusion (PLIF) in Hospital Raja Perempuan Zainab II from June 2007 till June 2010. Patients’ clinical symptoms were assessed using Oswestry Disability Index (ODI) pre- and postprocedure. MRI lumbosacral pre and post PLIF were analysed in axial and sagittal views. The depth of the lateral recess and exit foramina were measured at mid zone, exit zone and far lateral zone, and compared pre and post PLIF. The height of the disc spacer was measured at mid sagittal views. Mean difference of lateral recess and exit foramina size before and after procedure were analysed using paired t-test, and correlated with ODI score using Pearson’s correlation test. Correlation test was also used to determine whether disc spacer height is a good predictor for improvement of lateral recess and exit foramina size. Results: From 39 patients underwent PLIF in Hospital Raja Perempuan Zainab II, 25 patients fulfilled the inclusion criteria with 43 lumbar segments available for analysis. Increment of lateral recess and exit foramina measurements post PLIF were observed at all levels which was statistically significant (p<0.05). Improvement of clinical symptoms based on ODI score (p<0.05) was also noted. However, there was no significant correlation between patients clinical improvement and improvement of lateral recess and exit foramen (p>0.05). It was also noted that the height of the disc spacer was not a predictor for increment of exit foramen (p>0.05) Conclusion: Posterior Lumbar Interbody Fusion is proven to restore depth of lateral recess and exit foramen. Patients underwent PLIF had significant good surgical outcome. The difference of disc spacer height used in the procedure did not determine the increment of exit foramina. Therefore, current practice of using disc spacer height according to adjacent disc height is an acceptable method.